Interpreting the Nuclear Non-proliferation Treaty - Joyner, Daniel (Oxford : Oxford University Press, 2011)
The 1968 Nuclear Non-Proliferation Treaty is one of the most controversial instruments in international law. This text argues that countries with nuclear weapons misrepresent the Treaty to prevent other states from developing peaceful nuclear energy holding back nuclear disarmament in the process.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Treaty on the Non-proliferation of Nuclear Weapons, -- (1968); Nuclear nonproliferation; Nuclear arms control; Nuclear energy -- Law and legislation